(untitled) (Revista de Estudos da Linguagem, 2006)
The present literature on the use of computer in foreign languageclassroom points out the important role hypermedia plays to lexisteaching and learning in a foreign language. However, there aren’tstudies which address aspects of knowledge or competencesrequired for lexis learning mediated by hypermedia, so that it canbe more significant and efficient. Considering that, the presentwork is aimed at discussing a proposal of a lexical competencemodel for hypermedia environment, offering, in this way,theoretical support to teachers and researchers in lexis teachingand learning in this new scenery.